The Role of Corporate Governance in Constraining Earning Management - Dwi Jaya Kirana; Ekawati Jati Wibawaningsih; Aniek Wijayanti (DINASTI RESEARCH, 2020)
This study examines whether corporate governance measured by audit quality, ownership structure, and board of commissioners quality has an effective role in constraining earnings management in Indonesia. The sample of this research is 163 companies in non-financial sectors listed on the Indonesia Stock Exchange in the period 2014-2018. Regression analysis is used to test the research hypothesis. Discretional accruals were used to measure earning management. The results show that the audit firm’s reputation as a proxy of audit quality has a negative significant influence (at the 5% level) on earning management practices. Contrary to the hypothesis, we found that the size of the board of commissioners has a positive significant influence (at the 5% level) on earnings management. These findings provide practical advice for the government and shareholders in providing effective corporate governance mechanisms in constraining earnings management.